Análisis del nivel de ventas de la Empresa Electromuebles del cantón Babahoyo. - Mora Icaza, José De Jesús (2020)
The purpose of this case study was to analyze the different causes for which sales in the Electromuebles commercial decreased. During the start-up period the company had great success in its operations achieving levels in its sales that at the time covered its costs obtaining profit. As time goes by sales in the commercial have undergone variations with inclination largely towards low levels due to various causes such as high value in the past due portfolio, poor administrative management, lack of business policies, changed location commercial to a place, lack of confidence on the part of the owner manager, the large number of companies dedicated to commercialize similar products and the lack of liquidity that increased year by year making the manager who owns the commercial premises seek financing.